Continuous Manufacture and Scale-Up of Theophylline-Nicotinamide Cocrystals - Steven A. Ross; Andrew P. Hurt; Milan Antonijevic; Nicolaos Bouropoulos; Adam Ward; Pat Basford; Mark McAllister; Dennis Douroumis (MDPI AG, 2021)
The aim of the study was the manufacturing and scale-up of theophylline-nicotinamide (THL-NIC) pharmaceutical cocrystals processed by hot-melt extrusion (HME). The barrel temperature profile, feed rate and screw speed were found to be the critical processing parameters with a residence time of approximately 47 s for the scaled-up batches. Physicochemical characterization using scanning electron microscopy (SEM), differential scanning calorimetry (DSC), and X-ray diffraction of bulk and extruded materials revealed the formation of high purity cocrystals (98.6%). The quality of THL-NIC remained unchanged under accelerated stability conditions.